Early Weight Loss in Behavioral Treatment Predicts Later Rate of Weight Loss and Response to Pharmacotherapy. Issue 3 (24th May 2018) - Tronieri, Jena Shaw; Wadden, Thomas A; Chao, Ariana M; Pearl, Rebecca L; Alamuddin, Naji; Berkowitz, Robert I
Abstract: Background: Early weight loss (EWL) in the first 1–2 months of behavioral treatment is a strong predictor of later total weight loss. It is not clear whether participants with lower early losses lose less in ongoing treatment or simply fail to overcome the smaller initial loss. Furthermore, no study has tested whether EWL in behavioral treatment predicts response to a different treatment modality, such as pharmacotherapy. Methods: Data were from 170 participants with obesity (baseline BMI = 40.8 ± 5.8 kg/m 2, 87.6% female; 71.3% Black) enrolled in a two-phase trial. Data from the weight loss phase, which provided weekly lifestyle counseling and a meal replacement diet, were used to examine the relationship between 4-week EWL and subsequent rate of weight loss in behavioral treatment. Data from the maintenance phase, in which 137 participants who had lost ≥5% of initial weight were randomized to 52 weeks of maintenance counseling with lorcaserin or placebo, were used to determine whether EWL with behavioral treatment affects the benefit of pharmacotherapy. Results: EWL in the first 4 weeks of behavioral treatment (3.6 ± 1.7%) predicted greater total losses at Week 14 ( r 2 = 0.61, p < .001) and a faster rate of weight loss in the subsequent 9 weeks of the program ( p < .001). During the maintenance phase, lower EWL in behavioral treatment predicted a greater benefit of lorcaserin, in comparison with placebo, for the maintenance of a ≥5% loss at Weeks 24 and 52. Conclusions: These findings support recommendations to modify treatment for individuals with low EWL. Abstract : Lower early weight loss in behavioral treatment predicted slower weight loss in subsequent weeks of that program but was associated with a greater benefit of lorcaserin over placebo for weight loss maintenance.